Dispute Settlement in the Public Sector : The Canadian Scene - Goldenberg, Shirley (Relations industrielles / Industrial Relations, 1973)
A brief overview of the current provisions for impasse resolution at all levels of public employment is followed by a more detailled discussion of policy and practice in jurisdictions that grant the right to strike to the employees of senior levels of government. Finally, the author tries to identify some of the problems that complicate the settlement of disputes in the public sector and considers the challenge and the prospects of resolving these problems in the light of the Canadian experience.